Pathology of an iridescent virus in immature Culex pipiens L. (Diptera, Culicidae) - Muttis, Evangelina (2023)
Iridovirus in Culex pipiens was reported for the first time in 2012. Later studies of horizontal transmission were performed, in which an interaction with the parasite Strelkovimermis spiculatus acting as viral vector was recognized. In the present study, we observed aspects of the pathology produced by an invertebrate iridescent virus in laboratory infected immature Cx. pipiens as well as in infected immature Cx. pipiens in the field. In the laboratory infected larvae, the infection and mortality were asynchronous. Signs of infection in larvae exposed to the virus were observed between the second and the fourth days post-exposure in 99% of the cases, while the highest daily record of visible infected larvae (52%) was observed on the third day post exposure. Moreover, 79% of confirmed virus infected larvae died in the first 10 days after exposure. The Median Lethal Time was eight days. Several tissues were found to be infected and the common sites of replication were the fat body, epidermis and epithelial derivatives, such as the imaginal discs and the tracheal epithelium. Moreover, infection in the salivary glands, gastric ceca and posterior gut have not been previously documented on other mosquito iridescent viruses.